Development and validation of the Islamic-based smoking cessation program module for young adults - Azmi, Junainah; Syed Elias, Sharifah Munirah; Nurumal, Mohd Said; Mohd Mokhtar, Hanida Hani; Sutantri, Sutantri (IIUM Press, 2022)
Objective: This study aims to develop and validate the new Islamic-based Smoking Cessation Program (ISCP) for undergraduate male smokers. Methods: The development of the intervention was based on the Intervention Mapping (IM) Protocol, where basic health education program planning activities involved four main steps which are; conducting a needs and capacity assessment of the program, developing the program, formative evaluation including; validating and implementing the program. A content validity level (CVL) was used to assess the content validity quantitatively, with a CVL of more than 70% being considered appropriate. Results: The module was found to have a high level of authenticity (content validity level = 79%). Revision and modification were completed based on the expert panel comments and suggestions to improve the module. Conclusion: The ISCP module has good content validity and can be used to assist undergraduate smokers in their cessation journey